(untitled) (Research, Society and Development, 2021)
The objective of this work was to indicate phytosociological parameters of species of the genus Handroanthus sp. in different sites and regions of the State of Pará. The data were collected from the Integrated Environmental Monitoring and Licensing System of the State of Pará and in scientific works. The region of occurrence, the number of individuals, the volume of wood in total cubic meter and per hectare, the size of the sample area or the 100% forest inventory, of environmental licenses in the years 2012 to 2016, as well as in scientific works, were recorded. These data generated maps that demonstrated that the genus Handroanthus sp. occurs in almost all mesoregions of the state. The Southeast and Northeast Paraense showed less occurrence and low density of the species. Sudoeste Paraense and Baixo Amazonas are places of greater occurrence of the genus and densities less than 0.4 trees / ha can be used as a reference in the analysis of forest inventories 100%.